BASE MODELS IN COMPUTER-BASED PEDAGOGICAL DIAGNOSTICS SYSTEM - Kolgatin, O. (Journal of Information Technologies in Education (ITE), 2012)
The structure of base models in a computer-based pedagogical diagnostics system is proved: the learning objectives model, the psychological and pedagogical model of student, the model of learning technology realisation. The structure of corresponding data bases of information system is suggested.